Autosomal genetic variation is associated with DNA methylation in regions variably escaping X-chromosome inactivation - Luijk, R; Wu, H; Ward-Caviness, C; Hannon, E; Carnero-Montoro, E; Min, J; Mandaviya, P; Müller-Nurasyid, M; Mei, H; Van Der Maarel, S; BIOS Consortium; Relton, C; et al. (Nature Publishing Group, 2018)
X-chromosome inactivation (XCI), i.e., the inactivation of one of the female X chromosomes, restores equal expression of X-chromosomal genes between females and males. However, ~10% of genes show variable degrees of escape from XCI between females, although little is known about the causes of variable XCI. Using a discovery data-set of 1867 females and 1398 males and a replication sample of 3351 females, we show that genetic variation at three autosomal loci is associated with female-specific changes in X-chromosome methylation. Through cis-eQTL expression analysis, we map these loci to the genes SMCHD1/METTL4, TRIM6/HBG2, and ZSCAN9. Low-expression alleles of the loci are predominantly associated with mild hypomethylation of CpG islands near genes known to variably escape XCI, implicating the autosomal genes in variable XCI. Together, these results suggest a genetic basis for variable escape from XCI and highlight the potential of a population genomics approach to identify genes involved in XCI.